2011
DOI: 10.1186/1472-6963-11-56
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a primary care-based telemonitoring intervention for home care patients with heart failure and chronic lung disease. The TELBIL study

Abstract: BackgroundTelemonitoring technology offers one of the most promising alternatives for the provision of health care services at the patient's home. The primary aim of this study is to evaluate the impact of a primary care-based telemonitoring intervention on the frequency of hospital admissions.Methods/designA primary care-based randomised controlled trial will be carried out to assess the impact of a telemonitoring intervention aimed at home care patients with heart failure (HF) and/or chronic lung disease (CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…Figure 1 outlines the general study design, showing the flow of patients through the trial. Further details concerning the methodology of the trial can be found in the published study protocol [12]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 outlines the general study design, showing the flow of patients through the trial. Further details concerning the methodology of the trial can be found in the published study protocol [12]. …”
Section: Methodsmentioning
confidence: 99%
“…The trial protocol has been published elsewhere [12]. The main objective of the study was to assess the effect of a primary care-based telemonitoring system on the number and length of hospital admissions in patients with HF and/or CLD at 12 months post-randomisation compared with the standard health care practice.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is part of a home telemonitoring clinical trial (the TELBIL study) conducted across 23 health centres of the Bilbao Primary Health Care Region, Basque Country (Spain) [36]. The health region serves a catchment population of 390,000 people, of whom around 27% are over 60 years old.…”
Section: Methodsmentioning
confidence: 99%
“…344,345 A home telehealth programme for patients with severe COPD, implemented as a cluster RCT in the Madrid region. 346 Home enteral nutrition support for children with chronic diseases across Spain.…”
Section: Box 4 Selected Telecare Pilot Projects In Spainmentioning
confidence: 99%